2018
DOI: 10.1016/j.immuni.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor STAT6 Mediates Direct Repression of Inflammatory Enhancers and Limits Activation of Alternatively Polarized Macrophages

Abstract: SummaryThe molecular basis of signal-dependent transcriptional activation has been extensively studied in macrophage polarization, but our understanding remains limited regarding the molecular determinants of repression. Here we show that IL-4-activated STAT6 transcription factor is required for the direct transcriptional repression of a large number of genes during in vitro and in vivo alternative macrophage polarization. Repression results in decreased lineage-determining transcription factor, p300, and RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
195
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(213 citation statements)
references
References 49 publications
14
195
3
1
Order By: Relevance
“…In other words, RACK1 could inhibit the expression of IL‐6, CCL5 and CSF in OSCC cells and their secretion and then inhibit macrophage recruitment to the TME of OSCC. Furthermore, during the polarization process of macrophages, AP‐1, NF‐κB and STAT1 activation is required for M1 polarization, and mTOR, PPARγ/δ and STAT6 activation is critical for M2 polarization (Czimmerer et al , ; Zhu et al , ). Our study demonstrated that both M1 and M2 key activation factors, such as AP‐1, NF‐κB, STAT1 mTOR, and PPARγ, were significantly increased after RACK1 was silenced in OSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, RACK1 could inhibit the expression of IL‐6, CCL5 and CSF in OSCC cells and their secretion and then inhibit macrophage recruitment to the TME of OSCC. Furthermore, during the polarization process of macrophages, AP‐1, NF‐κB and STAT1 activation is required for M1 polarization, and mTOR, PPARγ/δ and STAT6 activation is critical for M2 polarization (Czimmerer et al , ; Zhu et al , ). Our study demonstrated that both M1 and M2 key activation factors, such as AP‐1, NF‐κB, STAT1 mTOR, and PPARγ, were significantly increased after RACK1 was silenced in OSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this study that GPS2 depletion did not influence IL-4/ STAT6-dependent repression of Abca1, further supporting the LPS/p65 selectivity of the GPS2/ABCA1 pathway. However, given the genomic colocalization of STAT6 and GPS2 at many IL-4-regulated gene loci, the potential interplay of these 2 factors remain to be explored (36,38). Of interest is further that depletion of HDAC3 in RAW cells reduced Abca1 expression, the opposite of what would be expected if HDAC3 solely functions as a key component of the corepressor complex.…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate the role of GPS2 in modulating signal-dependent Abca1 expression in macrophages, we examined IL-4/STAT6 signaling linked to alternative M2 macrophage activation, as it was reported to inhibit Abca1 expression in mouse macrophages (38). ChIP-seq analysis from published BMDM datasets suggests colocalization of GPS2 with the major IL-4-induced TF STAT-6 at both the Abca1 promoter and enhancer (Supplemental Fig.…”
Section: Lxr Activation Of Abca1 Does Not Require Gps2 But Lxr Transmentioning
confidence: 99%
“…There is extensive crosstalk in the polarization programs in populations of macrophages presented with opposing cues 14,15 ; however, the complexity of macrophage polarization has not yet been explored at single-cell resolution. Such single-cell measurements are important because macrophage populations display significant cell-to-cell heterogeneity in their responses even following acute stimulation with LPS 1618 .…”
Section: Introductionmentioning
confidence: 99%